Care models for people with chronic diseases: integrative review - Elis Martins Ulbrich; Ângela Taís Mattei; Maria de Fátima Mantovani; Alexandra Bittencourt Madureira; Luciana Puchalski Kalinke (Universidad de Antioquia, 2017)
Objective. To identify the care models and the impact of the use of these in the care of people with chronic diseases reported in the literature in the years 2000 to 2014. Methods. Integrative literature review in which the following guiding question was adopted: Which care models are used in the care of patients with chronic diseases and what impacts can be verified through their application? We consulted the bibliographic databases Virtual Health Library, LILACS, MEDLINE, Spanish Bibliographic Index of Health Sciences and the Database of Nursing. Results.The sample consisted of 17 articles on the topic of interest. Three categories emerged from the analysis: healthcare costs, model-based care experience, and patient autonomy. The articles addressed self-management, case management and care model for people with chronic diseases. The major impacts on the use of the models were: a better relationship between the patient and the health professional, an increase in the autonomy of the person with chronic illness, and a reduction in personal and health care expenditure. Conclusion. The use of care models for people with chronic diseases presents benefits to the patient and to the health system. Nurses must actively participate in the application of these care models of people with this type of illness. How to cite this article: Ulbrich EM, Mattei AT, Mantovani MF, Madureira AB, Kalinke LP.  Care models for people with chronic diseases: integrative review. Invest. Educ. Enferm. 2017; 35 (1):